Specific Intermolecular Interactions of Organic Compounds - Baev, Alexei K.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Prof. Baev presents in his book the development of the thermodynamic theory of specific intermolecular interactions for a wide spectrum of organic compounds: ethers, ketones, alcohols, carboxylic acids, and hydrocarbons. The fundamentals of an unconventional approach to the theory of H-bonding and specific interactions are formulated based on a concept of pentacoordinate carbon atoms. New types of hydrogen bonds and specific interactions are substantiated and on the basis of the developed methodology their energies are determined. The system of interconnected quantitative characteristics of the stability of specific intermolecular interactions is presented. The laws of their transformations are discussed and summarized. The new concept of the extra stabilizing effect of isomeric methyl groups on the structure and stability of organic molecules is introduced and the destabilization action on specific interactions is outlined.
Reverse Dative Bond in Organic Compounds, Molecular Complexes and Inconsistency of the sp3-Hybridization Model with Respect to Carbon Atom -- Nontraditional Approaches to Thermodynamic Analysis of Liquid Organic Compounds -- Types and Energies of Specific Intermolecular Interactions in Ethers and Organic Cyclic Oxides -- Specific Intermolecular Interactions of Ketones -- Types and Energies of Hydrogen Bonds and Specific Intermolecular Interactions in Alcohols -- Specific Intermolecular Interactions and H-Bonds in Aldehydes and Esters -- Types and Energies of Specific Intermolecular Interactions in Carboxylic Acids -- Specific Intermolecular Interactions in Hydrocarbons.
Keywords: Chemistry; Chemistry, Organic; Chemistry, Physical organic; Chemical engineering; Chemistry; Theoretical and Computational Chemistry; Organic Chemistry; Physical Chemistry; Industrial Chemistry/Chemical Engineering